Inflammatory processes involved in the alteration of liver function biomarkers in adult hospitalized patients treated with parenteral nutrition - Llop Talaveron, Josep M.; Suárez-Lledó Grande, Ana; Leiva Badosa, Elisabet; Bas Minguet, Jordi; Climent Martí, Joan; Poyatos Cantón, Elisabet; Badia Tahull, María B. (Frontiers in Nutrition, 2023)
INTRODUCTION Liver damage has been associated with the accumulation of phytosterols (PS) in patients treated with parenteral nutrition (PN). We aimed to study the association of inflammatory markers with liver function biomarker (LFB) alterations in patients treated with PN containing PS. MATERIAL AND METHODS Prospective observational study. Simple linear and stepwise multiple linear regression tests and interactions were performed. RESULTS Nineteen patients were included. In the multivariable model, determinations based on LFBs as dependent and phytosterols (and their fractions) as independent variables showed an association between increases in gamma-glutamyltransferase (GGT) and lanosterol (p <0.001), stigmasterol (p <0.001), interleukin-10 (IL10) * total phytosterols (Phyt) (p <0.009), Tumor Necrosis Factor (TNFα) * Phyt (p< 0.002), IL10 * sitosterol (p <0.002), TNFα * sitosterol (p< 0.001), IL10 * campesterol (p <0.033), IL10 (p <0.006 and p <0.015), TNFα (p <0.048 and p <0.027). Increases in alanine aminotransferase (ALT) were associated with Phyt (p <0.006), lanosterol (p<0.016), C-Reactive Protein (CRP) * campesterol (p <0.001), interleukin-6 (IL6) * stigmasterol (p< 0.030), CRP (p <0.08) and IL6 (p < 0.042). Alkaline phosphatase (AP) increases were associated with CRP (p <0.002). DISCUSSION Inflammation in the presence of plasmatic PS seems to have a synergistic effect in impairing liver function, mainly altering GGT but also ALT.